Higher Education Piano Learning Management in North Eastern Thailand - Namsanga, Pariyat; Sapaso, Asst. Prof. Dr. Pongpitthaya; Pantasri, Asst. Prof. Dr. Pittayawat (Journal for Developing the Social and Community, 2019)
The purpose of the current study was to study higher education piano learning management in north eastern Thailand. Survey research approach was employed as the main methodology. The samples were 9 instructors teaching in 9 universities in north eastern Thailand. The 4 aspects of the study were curriculum, piano learning management, evaluation and assessment, and managerial difficulties of piano instruction. The instruments were an interview form and an observation form. The results of the study were as follows. The results of the study indicated that at the level of higher education, the international curriculum was adapted to the contexts with the learning period taking 6-8 semesters were found. The 1-2 hour off-curriculum classes were also found once or twice a week. 3 level – lower, intermediate, and high of learning management were found. The parallel courses included music theories, chorus arrangement, music history, band performance, computer in music, and piano literature. The difficulties found in the management of piano instruction were lack of expertise instructors, learning resources, and low music proficiency learners recruited at the first stage of the curriculum. The recommendations in piano learning management were the instruction of standardized basic knowledge of piano, chooses of practicing songs, time management, mutual agreements between learners and instructors, and continuum of learning and practices